(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the stages of formation and development of agricultural culture in ancient Khorezm based on archaeological, naturalgeographical, and cultural sources. It analyzes the evidence related to ancient riverbeds of the Amu Darya, irrigation systems, agricultural tools, and religious beliefs. The paper also highlights the socio-economic and cultural significance of agriculture in the historical development of society